Antidiabetic and antioxidant profiling of 67 African trifoliate yam accessions by planar on-surface assays versus in vitro assays - Aiyedun, P.O.; Sonibare, M.A.; Gueye, B.; Albach, D.C.; Heil, J.; Morlock, G.E. (Elsevier, 2025)
Trifoliate yam (Dioscorea dumetorum) is traditionally used to treat diabetics in Nigeria. However, almost no information is available on its antidiabetic constituents and their natural variance. Hence, the activity of methanolic tuber extracts of 67 trifoliate yam accessions from the largest collection in Africa was proven by four colorimetric antidiabetic and antioxidant in vitro assays, as diabetes is also linked with oxidative stress. For the first time, selected accessions were also analyzed by planar bioactivity profiling. It has a comparatively higher, more differentiated information content, is more sustainable in terms of material consumption, and enables straightforward compound prioritization and characterization. Up to a dozen individual antioxidant zones were revealed as well as one prominent zone inhibiting α-glucosidase and α-amylase. The latter inhibition zone was tentatively assigned to palmitic, linoleic, oleic, linolenic, oxo-nonanoic fatty acids by direct elution to heated electrospray ionization high-resolution mass spectrometry.